Picoseconds Dark Pulse Zirconia-Yttria-Aluminium-Erbium-doped Fiber Laser - Markom, Arni Munira; Muhammad, Ahmad Razif; Mohd Yusoff, Zakiah; Mukul, Chandra Paul; Harun, Sulaiman Wadi (2020)
A 3.4 picoseconds dark pulse fiber laser was successfully generated using Zirconia-YttriaAlumina-Erbium-doped fiber laser (Zr-EDF) cavity with graphene oxide as saturable absorber.The laser cavity was 11.5 m long with the group delay dispersion of -0.04 ps2. Themultiwavelength optical spectrum provides 1 MHz repetition rate and 67.8 dB optical signal tonoise, defines the high stability of the dark pulse. A strong nonlinearity and high birefringenceof the Zr-EDF and GOSA cause the pulse turn down to dark region. An ultrafast dark pulse is demand due to low interference and excellent stability in the existence of noise that are requiredfor high efficiency and accuracy demanding by biomedical devices.